Estimated insulin sensitivity in Type 1 diabetes adults using clinical and research biomarkers. (September 2020) - Januszewski, Andrzej S.; Sachithanandan, Nirupa; Ward, Glenn; Karschimkus, Connie S.; O'Neal, David N.; Jenkins, Alicia J.
Highlights: Euglycaemic hyperinsulinaemic clamps were conducted in 28 adults with Type 1 diabetes. Using 38 traditional and novel biomarkers, a panel of formulae were derived to estimate insulin sensitivity using an exhaustive search method, accounting for up to 62% of the variability therein. Relationships with body habitus, sex, pulse pressure, lipids, adipokines and inflammation were noted. Correlations between measured insulin sensitivity and other published formulae estimating this were at best modest. A panel of biomarkers to estimate insulin sensitivity in Type 1 diabetes is available for testing in other clamp studies, and in clinical trials and practice. Abstract: Aims: Insulin resistance in people with type 1 diabetes (T1D) is associated with increased risk of chronic complications and death. The gold standard to quantify insulin sensitivity, a euglycaemic hyperinsulinaemic clamp, is not applicable to clinical practice. We have employed clamp studies to develop a panel of formulae to estimate insulin sensitivity in adults with T1D for use in clinical practice and trials. Methods: Clamps were conducted in 28 adults with T1D, who were also characterised with 38 clinical and research biomarkers. Exhaustive search analysis was used to derive equations correlating with clamp-quantified glucose disposal rate (GDR), GDR/plasma insulin (M/I) and log10 M/I. Results: Measured insulin sensitivity correlated with BMI, WHR, HDL-C, adipokines and inflammation markers on univariate analysis. Exhaustive search analysis derived three formulae correlating with clamp-derived GDR and logM/I ( p  < 0.0001), accounting for ≈62% of their variability. A formula using gender, age, HDL-C, pulse pressure and WHR performed as well as those containing inflammation and adipokine measures. Conclusions: The performance of formulae using routinely available parameters with/without research biomarkers in clinical studies and trials, particularly related to future complications, relevant lifestyle interventions, insulin delivery modes and insulin sensitisers is merited.